2021
DOI: 10.1136/gpsych-2021-100496
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of internet addiction among college students in the Indian setting: a systematic review and meta-analysis

Abstract: BackgroundThe internet is an integral part of everyone’s life. College going adolescents are highly vulnerable to the misuse of the internet.AimsTo estimate the pooled prevalence of internet addiction (IA) among college students in India.MethodsLiterature databases (PubMed, Web of Science, Scopus, EMBASE, PsycINFO and Google Scholar) were searched for studies assessing IA using the Young Internet Addiction Test (Y-IAT) among adolescents from India, published in the English language up to December 2020. We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 68 publications
(33 reference statements)
2
36
0
Order By: Relevance
“…The prevalence of problematic social media use has been found to be rather high in low-and middle-income countries. For example, 15.2% of college students in China have problematic social media use [11], and 19.9% of college students in India that use social media [12]. Problematic social media use has begun to be detrimentally linked to college students' mental health [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of problematic social media use has been found to be rather high in low-and middle-income countries. For example, 15.2% of college students in China have problematic social media use [11], and 19.9% of college students in India that use social media [12]. Problematic social media use has begun to be detrimentally linked to college students' mental health [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, problematic internet use was reported by 21% of Spanish university students ( 28 ). Moreover, it was 19.9% of Indian college students ( 29 ). A recent meta-analysis study has reported the overall pooled prevalence of internet addiction by 34.53% among African high school and university students ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the participants in our sample were all university students. This choice was made bearing in mind the results of recent meta-analyses conducted in different countries that have shown a high prevalence of Internet addiction in this population [e.g., ( 87 , 158 , 159 )] and have raised the urgence to orientate policy strategies to this emerging issue for young adults. However future research will be needed to replicate these findings in other groups.…”
Section: Discussionmentioning
confidence: 99%